Potency and stability of a trivalent, catalytically inactive vaccine against botulinum neurotoxin serotypes C, E and F (triCEF). (March 2020) - Webb, Robert; Wright, Patrick M.; Brown, Jennifer L.; Skerry, Janet C.; Guernieri, Rebecca L.; Smith, Theresa J.; Stawicki, Christopher; Smith, Leonard A.
Abstract: Botulism is an acute neuroparalytic affliction of the motor and autonomic neurons caused by the toxins produced from Clostridium botulinum and related bacterial strains. The botulinum neurotoxins, or BoNTs, consist of a phylogenetically diverse group of highly potent protein toxins. Current medical interventions for confirmed cases of botulism are limited to immediate administration of antitoxins and respiratory support. There is currently no licensed vaccine against botulism in the United States. The most widely distributed botulism vaccine was a pentavalent BoNT toxoid (PBT) against serotypes A-E administered until 2011 under an investigational new drug license. A binary vaccine composed of the recombinant, non-toxic, receptor binding domains (RBD) of serotypes/A1 and/B1 has completed a phase II clinical trial, but has yet to attain full licensure. We have previously published data demonstrating catalytically inactive, full length botulinum neurotoxin holoproteins (ciBoNT HPs) against serotypes/A1, /B1, /C1, /E1 and/F1 provide equivalent or superior potency against parental and dissimilar subtype toxins as compared the RBD vaccines. Here we describe the consistent potencies of the three independent lots each of ciBoNT/C1, /E1, and/F1 HPs against substantial monovalent challenges of the parental toxins. We also present data that a trivalent formulation of ciBoNT/C1, /E1 and/F1 (triCEF) maintains potency against both monovalent and polyvalent toxin challenges when stored as an adjuvanted vaccine at 4–8 °C for up to 2 years. Highlights: Consistent potency of three independent lots each of ciBoNT/C1, /E1 and/F1 vaccines. A trivalent vaccine protects against both individual and combined toxin challenges. A trivalent botulism vaccine stored at 4 °C maintains potency up to 2 years. Receptor domain mutations increase safety index of atoxic BNT protein antigens.